Effect of a Single Dose of Cadmium on Pregnant Wistar Rats and their Offspring - Díaz, María del Carmen (2014)
Cadmium (Cd) is a well-known toxicant targeting many organs, among them placenta. This heavy metal also has embryonary and foetal toxicity. This study was undertaken to analyse the effect of a single Cd dose administered at 4, 7, 10 or 15 days of gestation on the offspring of pregnant rats sacrificed at 20 days of gestation. Cadmium chloride was administered subcutaneously at 10 mg/kg body weight to Wistar pregnant dams; control animals received a proportionate volume of sterile normal saline by the same route. Maternal uteri, livers, kidneys and lungs, and foetuses were examined at necropsy. Samples of maternal organs and whole foetuses were collected for histopathologic examination, determination of Cd levels and staining by the Alizarin red S technique. Results revealed a clear embryotoxic and a teratogenic effect of this heavy metal, the former as a significant increase in the number of resorptions, and the latter as significant decrease of the gestational sac weight, and the size and weight of foetuses of Cd-treated dams as well as induced malformations in skull bones, vertebrae and thoracic, and pelvian limbs. The deleterious effects found were similar to those previously reported for other animal models suggesting a high conservation of the pathogenic mechanisms of Cd. Additionally, many of the addressed aspects showed a slight dependence on the time of administration of the toxic that might be due to the accumulation of the metal in different organs, as we were able to demonstrate by the analysis of its concentration.